Application of the rule-based system method to determine the type of crops based on altitude and rainfall - Gunawan, Gunawan; Firmansyah, Akhmad Lutfi; Santoso, Bayu Aji (Jurnal Mantik, 2024)
Applying the rule-based system method to determine the type of agricultural crop based on altitude and rainfall is essential in increasing productivity and efficiency in modern agriculture. This study aims to develop and implement a rules-based system to recommend suitable plant types by analyzing altitude and rainfall data in the Tegal District. The research method includes experimental design, quantitative analysis, and model validation using data from the Central Bureau of Statistics and various other internet sources, covering January 1 to December 31, 2023. The results showed that this rule-based system effectively provides accurate recommendations with an average accuracy rate of 85% and an error rate of 15%. This system helps farmers make informed decisions about crop selection, reducing crop failure risk and contributing to sustainable agricultural practices. Future research suggests integrating real-time weather prediction technology and additional environmental variables to improve the precision of recommendations and expand the applicability of these systems to other areas with similar characteristics